Features of socialization of computer gamers - Makarchuk, Anna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article discusses the features of the socialization of computer gamers. Among the key problems of modern society an important place is occupied by the problem of regulation of social behavior of minors. Of particular importance in this perspective, acquires the phenomenon of socialization, because it accumulates the dynamic characteristics of the formation and development of the orientation vector of the whole conduct of man in society. Thus, the process of socialization of minors acute in studies of the mechanisms of appearance as Pro-social and delinquent behavior. For a short history of independent Ukraine has undergone profound changes in different spheres of life. Fast paced scientific and technological development has led to the wide spread of computer technologies that are increasingly captured various spheres of social life, penetrating in this way, and in the entertainment industry. Today, computer technologies have a significant impact on the public consciousness, and the formation of the individuality of each person. The twenty-first century – a period of rapid informatization and computerization of society had a particular impact on minors who have obtained a new form of leisure. With regard to their personal immaturity, that minors are the most vulnerable category, which falls under the influence of various forms of computer technology.